Assessing productivity channels of human capital in the Southern African development community: New insights from women's empowerment - Abiola John Asaleye; Kariena Strydom (Journal of Risk and Financial Management, 2022)
There is massive and growing volume of literature on human capital and productivity. However, there is little emphasis on the growth channels of human capital, particularly on women's empowerment, despite its theoretical underpinning and relevance in the Southern African Development Community (SADC). Understanding the effective channels of human capital is essential for policymakers in promoting sustainable growth and improved welfare. Given this, the study examines the effect of women's empowerment through the "factor accumulation channel" and the "productivity channel" on SADC using cross-sectionally augmented autoregressive distributed lag (CS-ARDL) and the Dumitrescu-Hurlin non-causality test. Evidence from short- and long-run effects using the CS-ARDL shows that the factor accumulation and productivity channels of women's empowerment have not benefited productivity growth in the SADC, although causality flows from the human capital indicators to productivity growth. The vital way for policy to boost productivity in SADC is to improve investment in female education and ensure that human capital is appropriately distributed and matches the economy's dynamic demands. Based on the findings, the study suggests developing a framework to ascertain from time to time the marginal benefits of investment in female education compared to the marginal costs, both at the levels of the factor accumulation channel and the productivity channel in SADC.
Keywords: D02; O17; P31; C54; 650; productivity; human capital; women’ s empowerment; long-run; causality